The experience of mothers of children with autism : a hermeneutic phenomenological study - Sólveig Guðlaugsdóttir (2009)
Meistaraprófsritgerð við Royal College of Nursing Institute (London) og Háskólann á Akureyri, 2002. Mothers of children with autism experience their life as a never-ending struggle for their children. Whereas 'normal' children mature and grow out of the parental nest, autistic children remain under the care of their parents for as long as the parents are able to sustain them. The purpose of this study was to explore the experience of mothers of autistic children and gain new perspectives of how parents and professionals work together. Data consisted of transcripts from indept interviews with ten Icelandic mothers of children diagnosed with autism. The mothers all participated voluntarily and their age was from thirty four to forty nine years of age. The methodology used in the study was hermeneutic phenomenology building on Gadamer's philosophy and van Manen's description of thematic analysis. In the study the emerging themes of the transcribed interviews were grouped into five categories based on the discussions of the five overriding topics. These topics were; becoming a mother of a child with autism; coping and taking care of self; the father of the child; where to seek help; and the need for support from professionals. The results are described using quotations from the participants. The findings revealed that the participants experienced themselves as being alone in the period of the discovery of the child's handicap, because other people did not se the same as they did. Even though the participants saw their role as caretakers for their children as a never-ending responsibility they all saw the importance of taking care of themselves as well. The participants' experience of chronic sorrow, anger and empowerment is consistent with research literature. Outstanding in this study was the participants' descriptions of how their love for their children was rewarded in the way they learned and grew through the experience of having these special children. The participants use of humour became evident and was an ...